Peran Financial Literacy dan Overconfidence dalam Pengambilan Keputusan Investasi: Suatu Tinjauan Kuantitatif - Syahaya, Jumara Tori; Pardosi, Armiaty Putri Cesaria; Arni, Arni; Nababan, Natalis Sabatini; Ningsih, Riyanti Ratna (Journal of Innovation in Management, Accounting and Business, 2024)
This research aims to explore the impact of Financial Literacy and Overconfidence on investment decisions among students of the Faculty of Economics and Business, Universitas Pamulang. Utilizing a quantitative method, data was collected from respondents who participated in the Capital Market School. The analysis revealed that individually, Financial Literacy and Overconfidence do not exert a significant influence on investment decisions. However, when examined together, they collectively yield a significant effect. The Regression Analysis results indicate that Financial Literacy does not exhibit a significant partial effect on investment decisions. Similarly, Overconfidence does not demonstrate a substantial partial impact on investment decisions. Nevertheless, when analyzed collectively, both factors influence the investment decisions of students.This study emphasizes the importance of strong financial literacy as a key aspect in making informed investment decisions, albeit without significant individual impact. Conversely, Overconfidence, representing excessive confidence in one's abilities or knowledge, does not directly impact investment decisions on a partial basis. However, jointly, both factors significantly influence investment decision-making. These findings provide a basis for financial education within higher education to further emphasize enhancing financial literacy and awareness of Overconfidence in personal financial management and investment decision-making. Subsequent research could consider additional factors that may affect investment decisions and broaden the scope to different respondent groups or more complex investment scenarios.